Efficacy of Fractional CO2 Laser in Treatment of Mild to Moderate Facial Atrophic Acne Scars (Medical Forum Monthly, 2021)
Objective: To evaluate the efficacy of fractional Co2 laser in the treatment of mild to moderate atrophic facial acne scarring.Study Design: Descriptive case series studyPlace and Duration of Study: This study was conducted at the Dermatology Department Unit-I, King Edward Medical University, Mayo Hospital, Lahore between Oct, 2014 to April, 2015.Materials and Methods: One hundred and fifty patients were included in this study. fractional Co2 laser (10,600nm) flounce was delivered with settings of 15-20mj/cm2, pulse duration upto 3ms, interval of 1ms, distance of 0.8mm, spot size 300 microm, single pass using the fractional mode. Total six treatments at 4 weeks interval were given and final assessment after 4 weeks of 6th session was done.Results: Mean age was observed 23.56±5.12 years. Out of 150 cases, 58 patients (38.7%) were males while remaining 92 patients (61.3%) were females. Mean acne scar count at baseline 4.94±1.36 and after 24 weeks mean acne scare count were 3.98±1.70. There were only 4 patients (2.7%) were married and 146 patients (97.3%) were unmarried. Distribution of cases by acne scar severity at baseline was as follows: 15 patients (10.0%) were having mild acne scars and 135 patients (90%) were having moderate acne scars. Acne scar severity after 24 week. 121 patients (80.7%) mild acne scars were seen and in 29 patients (19.3%) moderate acne scars were observed. Efficacy of fractional Co2 laser in the treatment of mild to moderate atrophic facial acne scarring were observed in 123 patients (82.0%).Conclusion: fractional Co2 laser appears to be effective and well tolerated for the treatment of mild to moderate atrophic facial acne scarring.